Improving DES Robustness for Text Encryption via Blum-Blum-Shub Key Generation - Moata, Omega Joel Patria; Vebiyatama, Andicha; Indra, Muhamad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The security vulnerabilities of the Data Encryption Standard (DES) require innovative enhancements to ensure data protection against modern threats. This study integrates the Blum-Blum-Shub (BBS) pseudorandom number generator with DES to enhance encryption robustness. By leveraging BBS’s randomness, the proposed method strengthens the 16-round block cipher structure of DES, improving security while maintaining computational efficiency. A Java-based desktop application is developed to implement this approach, ensuring data security without cloud reliance. Feasibility testing confirms successful encryption with an average processing time of 2 seconds, demonstrating both security improvements and practical applicability. Comparative analysis reveals that BBS integration enhances unpredictability, making decryption more challenging. The findings suggest that combining DES with BBS provides a viable solution to DES’s limitations. Future research may explore scalability, adaptation to diverse data types, and further optimizations to enhance encryption strategies against evolving cybersecurity challenges.